STUDI KOMPARASI KAPASITAS DAYA DUKUNG TIANG PANCANG SECARA ANALITIS TERHADAP HASIL UJI KALENDERING DAN PILE DRIVING ANALYZER (STUDI KASUS STRUKTUR SLAB ON PILE) PADA PROYEK PEMBANGUNAN JALAN TOL SEMARANG – DEMAK PAKET 2 - Aldila Winda Merytsa; Imas Istiari; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Semarang–Demak Toll Road Construction with length ± 27 km, built for reduce traffic jam in Semarang. Due to road construction must pass area with very soft soil conditions/swamp land. Where type soil this is known have power support very low. For resolve problem the so structure Street use structure Slab on Pile. Structure Slab on Pile consist from slab, pile head and Pile Foundation In analyzing the carrying capacity of piles analytically in this study, we used several methods such as the Meyerhof method, the Luciano Decourt method and the Schmertman method. Meanwhile, in our calendaring test, we used the Hilley method.On the Semarang–Demak Toll Road Development Project searching for comparison score power support ultimate Pile Foundation single by analytical with Calendaring data and PDA. Based on results calculation of value SPT data power support ultimate pile single on 44 m depth with method Mayerhof obtained 149.72 tons, for Luciano Decourt's method 210.0451 tons, Schmertman method 185,888 tons based on calculation Calendaring method Hilley 145,0251 tons and PDA obtained 148.73 tons.